Arterial Stiffness in a Cohort of Young People Living With Perinatal HIV and HIV Negative Young People in England - Mellin, J.; Le Prevost, M.; Kenny, J.; Sturgeon, K.; Thompson, L. C.; Foster, C.; Kessler, H. H.; Goswami, Nandu; Klein, N.; Judd, A.; Castro, H. (Frontiers in Cardiovascular Medicine, 2022)
Background: Antiretroviral therapy (ART) has increased life expectancy and consequently the risk of cardiovascular disease (CVD) in adults living with HIV. We investigated the levels and predictors of arterial stiffness in young people (YP) living with perinatal HIV (PHIV) and HIV negative YP in the Adolescents and Adults Living with Perinatal HIV (AALPHI) study. Methods: 213 PHIV and 65 HIV negative YP (42% siblings of PHIV) had pulse wave velocity (PWV) measurements taken (Vicorder software) from the supra-sternal notch to the middle of the thigh cuff. Average PWV was calculated from the three closest readings (≥3m/s and ≤12m/s) within 0.6m/s of each other. Linear regression examined predictors of higher (worse) PWV, including age, sex, HIV status and height as a priori, ethnicity, born outside UK/Ireland, alcohol/nicotine/drug use, weight, waist-to-hip-ratio, mean arterial pressure (MAP), caffeine 2h before PWV and nicotine on day of PWV. A separate PHIV model included CD4, viral load, years taking ART and ART regimen. Findings: 128(60%) PHIV and 45(69%) HIV negative YP were female (p=0.18), with median[IQR] age 18[16,20] and 18[16,21] years (p=0.48) respectively. Mean PWV was higher in the PHIV group than the HIV negative group (6.15(SD 0.83)m/s vs 5.93(0.70)m/s respectively, p=0.058). In multivariable analysis, having PHIV (adjusted p (ap)=0.020), being male (ap=0.002), older age (ap<0.001), higher MAP (ap<0.001) and nicotine use on day of measurement (ap=0.001) were predictors of higher PWV. The predictors were the same in the PHIV model. Interpretation: By late adolescence PHIV had worse PWV in comparison to HIV negative peers, and traditional risk factors for CVD (higher arterial pressure, being male and older age) were associated with higher PWV values. Regular detailed monitoring of cardiovascular risk factors should become standard of care for every young person with PHIV worldwide.